Phytochemical Profiling, GC-MS Analysis and Antibacterial Activity of Sida acuta leave Extracts Against Helicobacter pylori - Kamoldeen Ajijolakewu; Ayobami Elias Ajadi; S A Ayoola; Sheriffdeen Issa Bale; Taiwo Ayodeji Sorunke; Saheed Abayomi Onifade; Tomisin Oyawoye (UMYU Journal of Microbiology Research)
Study’s Excerpt: